2021
DOI: 10.1016/j.scitotenv.2021.147764
|View full text |Cite
|
Sign up to set email alerts
|

Natural ventilation strategy and related issues to prevent coronavirus disease 2019 (COVID-19) airborne transmission in a school building

Abstract: The World Health Organization (WHO) announced that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) may spread through aerosols, so-called airborne transmission, especially in a poorly ventilated indoor environment. Ventilation protects the occupants against airborne transmission. Various studies have been performed on the importance of sufficient ventilation for diluting the concentration of virus and lowering any subsequent dose inhaled by the occupants. However, the ventilation situation can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
90
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(107 citation statements)
references
References 32 publications
7
90
0
10
Order By: Relevance
“…The aerosols released by infected individuals through sneezing, coughing, talking, and breathing could accumulate in the air over time, increasing in concentration, if the elevator is not well ventilated. Smaller virus-containing particles can remain suspended in the air over long distances and time periods [ [ 19 ]]. Nishiura et al, 2020 [ [ 20 ]] found that transmission of COVID-19 in a confined space was 18.7 times greater compared to an open-air environment.…”
Section: Introductionmentioning
confidence: 99%
“…The aerosols released by infected individuals through sneezing, coughing, talking, and breathing could accumulate in the air over time, increasing in concentration, if the elevator is not well ventilated. Smaller virus-containing particles can remain suspended in the air over long distances and time periods [ [ 19 ]]. Nishiura et al, 2020 [ [ 20 ]] found that transmission of COVID-19 in a confined space was 18.7 times greater compared to an open-air environment.…”
Section: Introductionmentioning
confidence: 99%
“…Large dental treatment rooms have shown certain effects in terms of bioaerosol distribution [ 28 ]. As proposed by several authors, cross ventilation using the opening of windows and air purification devices were shown to be highly effective methods to reduce the risk of airborne transmission of COVID virus containing particles [ 29 , 30 , 31 , 32 ]. The course room (326.2 sqm) in contrast is equipped with 20 windows in total, each measuring 4 sqm and thanks to the fact that they can be opened this allows a rapid ventilation of the complete course room.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, mechanical ventilation systems may consume large amount of energy consumption (X. D. Cao, Dai, & Liu, 2016 ; Li, Shen, & Yu, 2017 ), which is not beneficial for the sustainable development of society. Thus, it is necessary to do research on the design of natural ventilation systems under the situation of epidemic prevention and control ( Corticos & Duarte, 2021 ; Park, Choi, Song, & Kim, 2021 ). Natural ventilation is a kind of passive green building technology using thermal pressure caused by the density difference of air inside and outside the building or the wind pressure caused by outdoor atmospheric movement to induce outdoor fresh air ( Gautam, Rong, Zhang, & Abkar, 2019 ; Moey, Chan, Tai, Go, & Chong, 2021 ).…”
Section: Introductionmentioning
confidence: 99%